EU's democracy promotion in Turkey - Matos, André (2015)
The European Union, as a regional actor and an example of stability and well-being, has embraced a set of principles it has stood for and which constitute its own identity. The diffusion of these values among third countries is one of the objectives of EU’s External Policy. Democracy can be found among those principles that are sought to be exported through comprehensive and complex strategies within different frameworks, such as neighbourhood relations, trade partnerships and the accession process. Focusing on the latter, candidates are object of an intensive process of Europeanisation that operates through different mechanisms, like socialisation and conditionality. Turkey, on the other side, has decided to apply for full membership several decades ago and, ever since, it has been object of pressure to Europeanise, which includes improving its unstable democracy. This case, however, is different from all other previous enlargements; for its special socio-cultural and civilisational features, Turkey constitutes a more complex novelty for the European Union. Therefore, this work aims study the influence of the European Union on the democratisation process of Turkey, focusing on the period ranging between 1999, the year the European Council recognised Turkey’s candidacy status, and 2009 that marks the 10-year period of that condition. It is the intention of this project to assess the impact of the European Union at that level through the study of the democratic evolution of the country and its co-relation with some independent variables related to the presence or pressure of the EU. As this is a challenging objective, in order to achieve it, it will require a deep reflection upon the central concepts like democracy and democratic consolidation and a diversified use of methodological techniques, such as statistical analysis and mathematical co-relations, historical analysis, literature review, content analysis and in-depth interviews. This study will privilege a Constructivist approach, emphasising the social construction of reality and the role of the ideational aspects – identity, perceptions.